Outcomes of Fecal Carriage of Extended-spectrum beta-Lactamase After Transrectal Ultrasound-guided Biopsy of the Prostate - ERTÜRK ŞENGEL, BUKET; TİGEN, ELİF; ALTINKANAT GELMEZ, GÜLŞEN; DURMUŞOĞLU, LÜTFİYE; KORTEN, VOLKAN; ODABAŞI, ZEKAVER (ELSEVIER SCIENCE INC, 2014)
OBJECTIVE To determine the prevalence of extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae (PE) fecal carriage in patients that undergo transrectal ultrasonography-guided biopsy (TRUSbx) and its relationship with post-biopsy infections. METHODS A prospective clinical study in 4 different tertiary hospitals between 2008 and 2010 was conducted. Four hundred men with sterile urine who were to undergo a TRUSbx because of the suspicion of prostate cancer were included and followed for 14 days after biopsy. Rectal swab culture specimens were acquired immediately before the procedure. Demographic data, prophylaxis choice, quinolone or any other antibiotic consumption within the past 2 months, history of prostatitis, repeat biopsy, intensive care unit admission, hospitalization, urethral catheterization, diabetes mellitus (DM), and steroid usage were recorded. RESULTS ESBL carriage was detected in 19% of patients and quinolone use within the last 2 months; other antibiotic use within the last 2 months and DM were found to be significantly associated (P < .05). Symptomatic urinary tract infection (UTI) on the third day after biopsy was seen in 9% of patients and was associated with fluoroquinolone (FQ) consumption before biopsy. Although ESBL-PE carriage was associated with post-biopsy UTI symptoms, it was not found to be associated with post-biopsy symptomatic UTI. Urosepsis was seen in 2 patients (0.5%) after biopsy, and both the patients were ESBL-PE carriers. CONCLUSION The presence of ESBL-PE was associated with DM and FQ consumption before biopsy. ESBL-PE carriage was associated with a high rate of post-biopsy UTI symptoms requiring further elucidation; however, it was not associated with microbiologically proven infections. FQ consumption before TRUSbx was also associated with post-biopsy infections. (C) 2014 Elsevier Inc.
Keywords: ESCHERICHIA-COLI; ANTIBIOTIC-PROPHYLAXIS; RISK-FACTORS; INFECTIOUS COMPLICATIONS; CORE BIOPSIES; PREVALENCE; ENTEROBACTERIACEAE; COLONIZATION; COMMUNITY; IMPACT